Features of legal support of genomic research in sports: foreign experience - Shevchenko, O. A.; Redkina, A. I.; Vorontsov, D. I. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze the existing foreign legislative frameworks and approaches for the sports-specific gene research.